Progress in Planar Optical Waveguides - Wang, Xianping; Yin, Cheng; Cao, Zhuangqi (Springer Tracts in Modern Physics, 2016)
This book provides a comprehensive description of various slab waveguide structures ranged from graded-index waveguide to symmetrical metal-cladding waveguide. In this book, the transfer Matrix method is developed and applied to analyze the simplest case and the complex generalizations. A novel symmetrical metal-cladding waveguide structure is proposed and systematically investigated for several issues of interest, such as biochemical sensing, Goos-Hänchen shift and the slow light effect, etc. Besides, this book summarizes the authors' research works on waveguides over the last decade. The readers who are familiar with basic optics theory may find this book easy to read and rather inspiring.